Reducing the VAT Gap Between 2016 and 2022: Lessons from Poland. Causes - Measures - Future Perspectives - Sarnowski, Jan; Selera, Paweł (Publishing House of The Angelus Silesius University of Applied Sciences, 2025)
The book is a translation of the original work published in Polish under the title “Ograniczenie luki VAT w Polsce w latach 2016−2022. Przyczyny – środki – dalsze perspektywy” by Jan Sarnowski and Paweł Selera. This study aims to examine and evaluate the effectiveness of the legislative, administrative, and technological measures implemented in Poland between 2016 and 2022 aimed at reducing the VAT gap, and to identify the key factors influencing the effectiveness of these measures. The analysis also seeks to identify additional perspectives for reducing the tax gap by improving the tax system and combating tax fraud. The main research problem of this paper is to answer the question: How did the reforms implemented in the area of tax policy and tax administration between 2016 and 2022 affect the reduction of the VAT gap in Poland? The problem focuses on assessing the effectiveness of these reforms, identifying the tools that had the greatest impact on reducing the gap, and understanding the reasons behind the effectiveness or ineffectiveness of these measures. The authors pose the following research hypothesis: The legislative, administrative, and technological reforms implemented in Poland between 2016 and 2022 have been effective in reducing the VAT gap, particularly by improving control mechanisms, automating settlements, and intensifying preventive measures against tax evaders. The first part of the monograph is dedicated to presenting the reasons behind the significant increase in the VAT gap during the first decade of the 21st century. It outlines the features of the EU VAT regulations that make them particularly vulnerable to the activities of organised crime groups, as well as the patterns of crimes committed by VAT mafias that exploit their weaknesses. It also provides data on the scale of the VAT gap in EU countries and the contribution of activities by the so-called ‘VAT mafias’ to this gap. The second part of the monograph presents measures to reduce the VAT gap, implemented successively at the supranational level by the European Union bodies and at the national level by individual Member States. This section also outlines directions for further ‘sealing’ of VAT legislation, presenting the proposals currently under debate by the European Commission and the recommendations from tax law academia addressed to both EU and national decision-makers. The third part of the monograph examines the measures implemented by Poland between 2016 and 2022 to reduce the VAT gap.
Keywords: VAT gap; Eurofisc; cross-invoicing; reverse charge mechanism; split payment; Uniform Control file; carousel fraud